2004
DOI: 10.1097/01.asn.0000120559.09189.82
|View full text |Cite
|
Sign up to set email alerts
|

The Parietal Epithelial Cell

Abstract: Abstract. Focal segmental glomerulosclerosis (FSGS) is a hallmark of progressive renal disease. Podocyte injury and loss have been proposed as the critical events that lead to FSGS. In the present study, the authors have examined the development of FSGS in Thy-1.1 transgenic (tg) mice, with emphasis on the podocyte and parietal epithelial cell (PEC). Thy-1.1 tg mice express the Thy-1.1 antigen on podocytes. Injection of antiThy-1.1 mAb induces an acute albuminuria and development of FSGS lesions that resemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 44 publications
6
72
0
1
Order By: Relevance
“…This finding is consistent with our previous reports. [17][18][19]27 In the current study, we examined podocyte regeneration under physiologic conditions and in models of glomerular hypertrophy. The choice to use these models was made for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with our previous reports. [17][18][19]27 In the current study, we examined podocyte regeneration under physiologic conditions and in models of glomerular hypertrophy. The choice to use these models was made for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of FSGS lesions and the participation of PECs have already been studied by us previously. [17][18][19] In those studies, we showed, in different Figure 2. Induction of progressive glomerular hypertrophy.…”
Section: Pec Invasion Onto the Glomerular Tuft In Fsgs Lesionsmentioning
confidence: 99%
“…The cellular composition of glomerular crescents in the a3KO mouse model does not appear to contain CD3 þ and CD19 þ lymphocytes, but is rather composed of proliferating visceral and parietal glomerular epithelial cells, and possibly macrophages, although their identification in glomerular crescents is challenging. [15][16][17][20][21][22] Overall, deletion of B-cell and T-cells in a3KO mice does not result in a protection from glomerular disease and loss of renal function. Proteinuria remains the same in the a3KO mice and the a3/Rag-1 DKO mice.…”
Section: Lymphocytes and Tissue Fibrosis Vs Lebleu Et Almentioning
confidence: 99%
“…Furthermore, a growing body of evidence has suggested that parietal epithelial cells are involved in crescent formation, with transdifferentiation of parietal epithelial cells and acquisition of new epitopes, shared by macrophages. [15][16][17][18][19][20][21][22][23] These results indicate that origins of glomerulonephritis still remain ambiguous, and mechanisms may differ according to the underlying renal disease.…”
mentioning
confidence: 99%
“…Humoral factors may play a role in inducing podocyte injury, which was shown in the work by Avila-Casado et al (33); rats injected with serum from patients with CG developed proteinuria, whereas rats injected with FSGS or normal human serum did not. Other mouse models have shown that an antibody-induced glomerular injury produced a CG-like pattern in three different strains of transgenic mice (34)(35)(36). A circulating factor has been postulated to play a role in podocyte injury in FSGS not otherwise specified in the form of high soluble urokinase receptor (37).…”
Section: Discussionmentioning
confidence: 99%